Masculine Girls in a Feminised Patriarchy: Negotiating the Sex/Gender System in Twenty-First Century Cinema - Trevenen, Claire Renee (Curtin University, 2016)
This thesis explores the narrative development of the girl’s gendered identity in relation to key male characters in a selection of films emerging at the beginning of the twenty-first century. It argues that this girl/man dynamic registers increasing cultural anxieties in relation to contextual shifts from this period, specifically the feminisation of working culture, through the way the narratives structure the girl’s potential for power in terms of a presumed disempowerment of the male subject.